Poética e Figuratividade: uma análise de Io (Ovídio, Metamorfoses, I, 583-747) - Mera, Ewerton de Oliveira [UNESP] (2013)
This paper presents the development of a scientific investigation that addresses the Latin text using theoretical concepts of Linguistic, Literary Poetic and Semiotic in order to focus mainly on aspects of the figurative expression. Therefore, the meaning effects raised by the perception through the reading of text were taken as baseline data to investigate the particular arrangement of language, responsible for expression of these effects. As a result of this investigation, a metalinguistic discourse was produced about the basic features of the poetic figurativity of the text. This analysis and description had a focus mainly on the first step of the procedures of figurativization, i.e., the figuration of the discourse, when a theme is coated by semiotic figures. In addition, reference notes were drafted to accompany the selected translation of support, with general comments about the culture (mythology, history, geography, philosophy, etc.), necessary data to an more comprehensive understanding of the text (these notes shall provide basic subsidies for reading the original Latin)